Community Perception and Participation of the Forestry Partnership Scheme on PT. Restorasi Ekosistem Indonesia Working Area in Jambi Province - Erwin Herwindo; Rosyani Rosyani; Eva Achmad (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Granting legal access to PT. REKI in ex. PT. The Asialog concession area in 2010 was marked by resistance accompanied by violence and claims by community groups (claimer). Conflict resolution with the Forestry Partnership approach resulted Forestry Partnership Recognition and Protection (Kulin KK) agreements for 79 heads of households who were members of 4 (four) groups. The question of this research is how the perceptions and participation of Kulin KK holders and the relationship between the two variables. The objectives of the study are to analyse the perceptions and participation and the relationship of its variables. This research is descriptive with a quantitative approach. The sampling technique used the census method with many respondents and 75 holders of legal access to Kulin KK. Perception and participation analysis and categorisation use 3 (three) point Likert scale and the score interval equation. The analysis of the relationship between perception and participation variables uses the Spearman correlation analysis. The results showed that the public perception of the provisions of the Forestry Partnership scheme was in the high category of 96% and 4% in the medium category, while the level of community participation was in the high category of 36%, 24% medium and 40% low. Perception and participation are negatively related.